Industrialized Timber Building Systems for an Increased Market Share – a Holistic Approach Targeting Construction Management and Building Economics. (2017) - Koppelhuber, Joerg; Bauer, Bernhard; Wall, Johannes; Heck, Detlef
Abstract: Advancements of recently developed timber products and their application within the prefabrication process require construction management processes to be standardized and unified. These processes then need to be scientifically proven with cross-company references. Apart from technical developments, especially in terms of cost savings and standardization of building procedures, professionalization also plays a fundamental role in providing practical application for a long term success in the market. The current demand for the mass appeal of timber is accompanied by various economical key factors in addition to the question of technical standardized system components, which provide long term stability regarding costs, consistent quality, construction management optimization and sustainability. According to this research paper, the integration of a consistent data workflow during the planning, production, and installation process allows for a significantly shortened construction period with major on-site cost reduction as well as for a sustainable approach to delivering a holistic construction management system for timber. The identified criteria and surveyed fundamentals are used to create general construction management methods for the branch. Additionally the applicability was analyzed consistently to determine future potential and generate appropriate and integral timber building systems. Modern timber construction methods are especially suitable for prefabrication because of the material-specific properties, its sustainable performance, the possibilities in prefabrication and easier assembly under dry construction conditions. For this reason a high productivity combined with excellent quality in short installation periods provides verifiable arguments for best practice examples in the area of construction management of modern timber building systems.